Peningkatkan Value Added dan Market Orientation Olahan Varian Jamur UMKM Cahaya Putra di Kabupaten Malang - Dwanoko, Yoyok Seby; Wahyu Setiyowati, Supami; Ba'diya Kusufa , Roni Alim (Jurnal Pemberdayaan Masyarakat, 2023)
Small and medium-sized enterprises (SMEs) Cahaya Putra as partners are located on Jl Masjid Arosidin Genengan Village, Pakisaji District, Malang Regency, East Java Province. The partner runs its business for 7 years, starting in 2015 until now. The production process carried out by partners still traditionally uses simple equipment. The type of processed mushroom food is still one product, namely mushroom chips. The taste is also still one taste, namely original. The packaging is still a standard form of plastic wrap size 0.10 pillow shape only and is less attractive. Marketing reach is still an area in Malang only and has not been marketed online. The community service methods used are observation, interviews, program planning and preparation, implementation of activities, and program evaluation. The results obtained are to provide appropriate production equipment procurement solutions as needed by the partner, improved quality, and packaging models of products that have attractive market competitiveness. The community service team conducts training and mentoring on financial management, how to conduct market research, and production control management, development of product variants, making new flavor variations through processed types of food raw materials for mushrooms, and online digital marketing training.